Early and Accurate Pathogen Identification Based on mNGS: Key to Timely Therapy for Mycoplasma Prosthetic Joint Infection - Zhenyuan Lin; Yang Chen; Zhenggui Yu; Zeyu Zhang; Yiming Lin; Wenming Zhang; Wenbo Li; Yufeng Guo; Xinyu Fang (Orthopaedic Surgery)
ABSTRACT Objectives Prosthetic joint infection (PJI) caused by Mycoplasma infection is relatively rare in clinical practice; all cases are primarily reported as individual case reports, and the characteristics of PJI induced by Mycoplasma infection have not been clearly studied. This case–control study was designed to systematically compare demographic profiles, clinical histories, diagnostic modalities, and therapeutic outcomes between Mycoplasma PJI and conventional bacterial PJI through retrospective analysis. Methods This retrospective single‐center study included 6 cases of simplex Mycoplasma PJI, 4 cases of mixed Mycoplasma PJI, 33 cases of Staphylococcus aureus , and 21 cases of Staphylococcus epidermidis infection from January 1, 2017 to January 1, 2024. Perioperative inflammatory markers, pathogen cultures, metagenomic next‐generation sequencing (mNGS) results, history of invasive urinary catheterization, clinical presentation, treatment, and rate of treatment success were recorded and analyzed for the four groups. Continuous variables were compared two‐by‐two between the four groups using independent t‐tests or the Mann–Whitney U test based on the distribution of the data. The categorical variables were compared using the chi‐square test or Fisher's exact test. Results The proportion of invasive urinary catheterization history in the mixed versus simplex Mycoplasma group was significantly higher than that in the Staphylococcus aureus and Staphylococcus epidermidis control groups (p < 0.05). Routine microbial culture positivity was significantly lower in the mixed versus simplex Mycoplasma group than in the control group (p < 0.01), but positive results for Mycoplasma can be detected by mNGS. Of note, one patient in the simplex Mycoplasma group was cured with targeted antibiotic‐only therapy and avoided surgery. There was no statistically significant difference in cure rates between the mixed and simplex Mycoplasma groups and the Staphylococcus aureus and Staphylococcus epidermidis control groups (p = 1.000). Conclusion Prior invasive urinary catheterization represents a significant risk factor for Mycoplasma PJI. The synergistic use of mNGS, optimized culture methods, and 16S rRNA PCR enables early detection of Mycoplasma. This multimodal diagnostic approach significantly enhances pathogen identification accuracy, minimizes diagnostic oversights, and provides essential guidance for effective therapeutic intervention.